Temperature- and pH-responsive injectable chitosan hydrogels loaded with doxorubicin and curcumin as long-lasting release platforms for the treatment of solid tumors - Li, Na; Lin, Jianjun; Liu, Chunping; Zhang, Qian; Li, Riwang; Wang, Chuang; Zhao, Chaochao; Lu, Lu; Zhou, Changren; Tian, Jinhuan; Ding, Shan (Frontiers in Bioengineering and Biotechnology, 2022)
ABSTRACT The treatment efficacy of chemotherapy in solid tumors is majorly limited by the dose-limiting toxicities due to the off-target effect and the heterogeneous distribution caused by dense extracellular matrix. In addition, the enhanced permeability and retention (EPR) effect within the tumor restrict the convection and diffusion of the drugs. To overcome these obstacles, in-situ forming hydrogel at the tumor was proposed to promote the drugs accumulation, retention and long-lasting release. In this work, we developed a thiolated chitosan (CSSH) hydrogel with a gelation point of 37 ℃. Due to the pH sensitive characteristics of disulfides, the prepared hydrogel facilitate the drug release in acidic tumor environment. Moreover, a double-drug release system of hydrophilic doxorubicin (Dox) and hydrophobic curcumin encapsulated by liposome (Cur-Lip) was designed to enhance the long-lasting therapeutic effects and reduce adverse side effects. The composite gels possess suitable gelation time of about 8~12 min under physiological conditions. The accumulative release ration at pH=5.5 was higher than that at pH=7.4 in the first 24 h while the Dox released about 10% and the Cur released slowly during the following 24 to 120 h. The cell assays results indicated that the Cur-Lip/Dox/CSSH gels could effectively inhibit the growth of cancer cells. The prepared in-situ formable Cur-Lip/Dox gels with long-term drug release capability have potential applications in tumor suppression and tissue regeneration after tumor resection surgery.